DINAMIKA PENGELOLAAN WAKAF DI NEGARA-NEGARA MUSLIM (ZISWAF: Jurnal Zakat dan Wakaf, 2017)
Waqf is one of the teachings of Islam that has been known since the time of the Prophet SAW, precisely in the second year of Hijriyah which began at the time of his prophethood in Medina and marked by the construction of the Quba Mosque. Then followed by the construction of the Nabawi Mosque built on the land of orphans of Bani Najjar. Waqf also occur during the time of Khulafa’ ar-Rasidin and also the companions thereafter to this day in some Muslim countries. Waqf has played important role in Muslim countries, such as Saudi Arabia, Jordan, Egypt, Kuwait and Turkey. In those countries, waqf is not merely in the form of worship related buildings but also in the form of farm field, educational institution, housing, cash, and capital stock.